Changes in lymphocyte subsets after short-term pharmacotherapy in patients with panic disorder - Kim, Youl-Ri; Park, Quehn; Yu, Bum-Hee (Psychiatry research, 2004)
Panic disorder is associated with a high frequency of comorbid immunological diseases, such as allergies and asthma, although the psychoneuroimmunology of panic disorder is relatively unexplored. The objective of this study was to determine whether panic patients have different immunological findings compared with normal healthy subjects and whether changes in immune function are associated with short-term pharmacotherapy. We also examined whether immunological variables were associated with clinical severity and serum catecholamine levels. Patients with panic disorder ( n=26) and healthy control subjects ( n=26) were recruited for this study. All patients were treated with paroxetine for 3 months. We measured the lymphocyte subsets, psychopathological characteristics and serum catecholamine (norepinephrine and epinephrine) levels. Panic patients did not differ initially from control subjects in peripheral lymphocyte phenotypic markers. After drug therapy, however, percentages of circulating CD3 +, CD4 + and CD8 + T lymphocytes were significantly increased, while the percentage of CD19 + B lymphocytes was significantly decreased in the patients. The difference in the percentage of CD8 + T lymphocytes before and after treatment was negatively correlated with pretreatment Global Clinical Impression scores. The lymphocyte subsets were not significantly associated with serum catecholamine levels in panic patients. In conclusion, panic patients showed increased CD3 +, CD4 + and CD8 + T lymphocyte proportions and a decreased B lymphocyte proportion after 3 months of drug therapy. This finding suggests that pharmacological treatment may affect immune function in panic patients.